Effects of Waterborne Cadmium Exposure on Its Internal Distribution in Meretrix meretrix and Detoxification by Metallothionein and Antioxidant Enzymes - Huang, Yao; Tang, Hongchao; Jin, Jianyu; Fan, Meng bi; Chang, Alan K.; Ying, Xueping (Frontiers in Marine Science, 2020)
Cadmium (Cd), one of the most toxic metals found in inshore sediments of China, is a persistent environmental contaminant capable of exerting irreversible toxic effect on aquatic organisms and their associated ecosystems. Although Cd is known to be toxic to marine animals, the underlying mechanism of this toxicity is not clear. In this study, Meretrix meretrix, a commercially and ecologically important species of clam, was exposed to different concentrations of cadmium chloride (0, 1.5, 3, 6, 12 mg L-1) for 5 days, and the levels of Cd accumulation, antioxidant enzyme activity and expression of metallothionein (MT) in the hepatopancreas, gill, foot and mantle were evaluated. The results revealed a sharp increase in Cd accumulation in the tissues in response to increased Cd2+ concentrations in the water, and significant differences in Cd accumulation were observed among the different tissues. Increased Cd2+ level in the tissues also led to a significant increase in malonaldehyde (MDA) content, caused by increased lipid peroxidation. The activities of superoxide dismutase (SOD) and catalase (CAT) also increased, peaking at different Cd2+ concentrations, depending on the tissue. Glutathione peroxidases (GPx) activity in the gill and mantle initially increased, but then decreased with increasing external Cd2+ concentration. In the hepatopancreas and foot, GPx activity was inhibited by Cd2+, even at low concentrations. Furthermore, Cd2+ also stimulated the expression of MT in all four tissues. However, the levels of reduced glutathione (GSH) andoxidized glutathione (GSSG) in the gill and mantle, as well as the GSH/GSSG ratios in all four tissues decreased with increasing external Cd2+ concentrations. Taken together, the results suggested that in M. meretrix, response to the toxic effect of Cd2+ might occur through a combination of mechanisms, which involve both enhanced antioxidant enzyme activities and the ability to bind and sequester Cd2+ via cysteine-rich molecules such as GSH and MT, both of which would eventually lead to the reduction of heavy metal-induced oxidative stress.